Pemberdayaan Santri melalui Budidaya Lele dengan Kolam Terpal di Pondok Pesantren Al Khusna, Dlingo, Bantul - Mutrofin, Mutrofin; Elfianto, Isa (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The purpose of this program is to create self-reliance, strengthen the economy, and improve students’ entrepreneurial skills. This is also based on utilizing the land around the boarding school, the effectiveness of implementation (which is quite reliable), and the benefits that can be felt by the boarding school. Methodology: This study used a participation action research approach with the author participating in the implementation of the program. The stages of implementation use the PDCA Model, which stands for the Plan-Do-Check-Act, the stages of quality development. Result: This empowerment program is carried out through six stages: planning, which consists of field observations and formulation of program objectives; the second stage of implementation, which involves conducting training and workshops on catfish farming and direct practice; and the third stage, which is carried out by monitoring care and maintenance, including feeding, cleaning the pond, and maintaining water quality. Fourth, follow-up, namely by developing tarpaulin ponds, maintaining and caring for catfish ponds, making organic feed, and becoming a motivator for the surrounding community. Limitation: This article focused on empowering students by developing a tarpaulin catfish farming system that was limited to harvesting and not continuing to sell. Contribution: This study contributes to the development of empty land by Pondok Pesantren Al Khusna. Increasing the knowledge and insight of students in catfish farming. Helping provides food to an Islamic boarding school environment.